Health Science Research at a Regional Level: Insights From South America; Comment on "The Roles of Regional Organisations in Strengthening Health Research Systems in Africa: Activities, Gaps, and Future Perspectives" - María Belén Herrero; Beatriz Nascimento Lins de Oliveira (Kerman University of Medical Sciences, 2023)
The article seeks to shed light on the role of regional organizations in strengthening health research systems in Africa, how they operate and how they work, as well as debts and future challenges. As can be observed also in South America, the continued strengthening of health research requires strategic thinking about the roles, comparative advantages, and capacity of regional organizations to facilitate the flourishing of health research systems. Health research is a strategic field for the transformation of socio-health inequalities on the one hand and the reduction of regional asymmetries on the other. Thus, regional organizations represent key actors in strengthening health research systems and the regional research agenda reinforces its sovereign condition in the autonomous definition of relevant topics and financing. In this process, integration mechanisms face a great challenge, as shown by the recent pandemic, not only in Africa but also in South America.